2015
DOI: 10.1016/j.jmmm.2015.05.079
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric magnetoimpedance effect in ferromagnetic multilayered biphase films

Abstract: effect in ferromagnetic multilayered biphase films, Journal of Magnetism and Magnetic Materials, http://dx.We investigate the magnetoimpedance effect in ferromagnetic multilayered biphase films. We verify that the films present asymmetric magnetoimpedance behavior and, by playing with the number of the repetitions of the base structure of the multilayer and the probe current frequency, we explore the possibility of tailoring the linear region around zero magnetic field in order to achieve higher sensitivity va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
(29 reference statements)
3
13
0
Order By: Relevance
“…Although the results of modeling describe main features of the AMI effect in bimagnetic multilayered films [12], some experimental data cannot be explained in the framework of the model proposed. It was observed that at frequencies above 1.5 GHz the shape of the impedance field dependence changes.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Although the results of modeling describe main features of the AMI effect in bimagnetic multilayered films [12], some experimental data cannot be explained in the framework of the model proposed. It was observed that at frequencies above 1.5 GHz the shape of the impedance field dependence changes.…”
Section: Resultsmentioning
confidence: 92%
“…To investigate the effect of the magnetostatic coupling and number of layers on the MI ratio, we use geometrical parameters of the bimagnetic multilayers studied experimentally [12]. The MI ratio DZ/Z 0 is defined as follows:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations